Implementing double-entry journal assisted with Instagram to foster engagement in EFL writing - Radina Anggun Nurisma; Wahyu Indah Mala Rohmana; Titik Lina Widyaningsih; Bambang Yudi Cahyono (Universitas Syiah Kuala, 2024)
Student engagement has critical impacts on students to excel academically. Integrating social media in a classroom can potentially affect students engagement. The present study aims to examine student engagement in EFL writing using Double-Entry Journal (DEJ) on Instagram, to examine the correlation between cognitive engagement and achievement, and to reveal the challenges in implementing DEJ. The researchers employed a mixed-method design, involving 42 undergraduate students from the English Department of one of the state universities in Indonesia, and obtained the data through questionnaires, writing portfolios, and Instagram documentation. The close-ended and open-ended questionnaires were distributed to the students, whereas writing portfolios and Instagram documentation were observed to examine the students writing performance. The collected data were managed, classified, and analyzed. The findings reveal that the students are behaviorally, cognitively, and affectively engaged by DEJ assisted with Instagram. There was a positive correlation between cognitive engagement and writing achievement. Yet, challenges had been found, including lack of interaction, student anxiety, and insufficient knowledge during the learning process. The challenges are lessened when teachers and peers offer support with DEJ. The results provide pedagogical implications for teachers to employ instructional strategies that promote engagement in all three dimensions, behaviorally, cognitively, and affectively to attain the students outcomes.